Analysis of the Risks of Using the Blockchain Technology in the Accounting and Audit of a Fuel and Energy Complex Enterprise - Ivanchenkova, Larysa; Shevtsiv, Liubov; Beisenova, Lyazzat; Shakharova, Aliya; Berdiyorov, Temur (International Journal of Energy Economics and Policy, 2023)
Blockchain is a modern, influential technology that is already transforming organizations and their business models in all business processes, including accounting and auditing. The article identifies and analyzes the risks of blockchain application in accounting and audits of fuel and energy companies. Areas of application of blockchain in accounting and auditing of fuel and energy companies have been determined, which include - integration of cryptocurrency into the accounting system of an energy company, creation of smart contracts, certification of renewable energy sources, automation of accounting and document flow, operational management of energy company assets, accounting of accounts consumption of energy and fuel resources. The risks of using blockchain technology in accounting and auditing of fuel and energy companies are systematized, which are grouped according to the following directions: high requirements of blockchain for energy consumption, lack of sufficient knowledge and skills of accountants in working with blockchain, technical, accounting and auditing problems. An example of choosing an economic risk management strategy of an energy company using maximax, Bayes, Laplace, Wald, Savage, Hurwitz criteria has been developed. The results of the research can be useful for accountants, auditors and managers of fuel and energy companies during the implementation and use of blockchain technology in practical activities.